Effects of a clostridial bacterin-toxoid administered subcutaneously at the base of the ear on stocker heifer performance, testosterone serum concentrations, and infrared thermal characteristics of the injection site and adjacent tissues - Sargeant, J.M.; Spire, M.F.; Paisley, S.I.; Minton, J. Ernest; Blasi, Dale A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 129-day field study was conducted to evaluate the effects of a clostridial bacterintoxoid administered subcutaneously at the base of the ear on heifer calf performance, surfaceear temperature, and testosterone concentration. Two hundred previously non-implanted heifers averaging 372 lb were assigned to one of four treatments: 1) Alpha-7 (clostridial toxoid) in left neck, Synovex-H in left ear (NL); 2) Alpha-7 in left neck, Synovex-H in right ear (NR); 3) Alpha-7 in right ear, Synovex-H in opposite ear (OP); and 4) Alpha-7 in right ear, Synovex-H in same ear (SM). On day 7, the right ear of each heifer was thermographically imaged. On trial days 7, 28, 59, and 87, jugular blood samples were collected to determine if placement of the clostridial vaccine reduced serum concentration of testosterone. Although vaccinating in the base of the ear increased (P<.01) ear temperature, daily gains through 59 days were similar (P$.44) for heifers injected in the neck (NL + NR) vs those injected in the base of the ear (SM + OP). Additionally, ear temperature and animal performance were similar (P$.11) for OP and SM placements of vaccine and implant. Testosterone concentrations were similar (P>.84) for heifers implanted in the right ear and vaccinated in the same side ear or neck.
Keywords: Beef; Infrared; Injection site; Growth implant; Heifers